Pontos de corte dos índices dopplervelocimétricos da artéria oftálmica para diagnóstico da pré-eclâmpsia: nova abordagem - Menêses, Vítor Fernando Silva de Campos (2020)
Objectives: To establish a cutoff value of the ophthalmic artery (OA) Doppler velocimetry to diagnose patients with pre-eclampsia (PE), comparing to healthy control patients. Methods: This prospective observational study enrolled 266 women in the second and third trimesters of pregnancy – 133 with PE and 133 healthy pregnant women. All patients were evaluated by OA Doppler sonography to assess its pulsatility index (PI), resistance index (RI), peak systolic velocity (PVS), second peak systolic velocity (P2), end diastolic velocity (EDV), and peak ratio (PR), and to compare the means using Student's T test. A Receiver Operating Characteristics (ROC) curve has been performed to establish the cutoff value, and estimate the sensitivity (S), specificity (Sp), and accuracy (A) of all variables. Results: The ROC curve analysis showed that P2 and PR were superior to the other parameters in PE diagnosis. We tested two cutoff values: (1) using PR ≥ 0.70, we obtained A: 88.72%, S: 81.95%, and Sp: 95.48% and (2) using PR ≥ 0.75, we obtained A: 86.24%, S: 74.43%, and Sp: 99.24%. Yet, by adopting P2 ≥ 21.5 cm/s, we obtained A: 87.59%, S: 84.96%, and Sp: 90.22%. The association of PR ≥ 0.70 and P2 ≥ 21.5 cm/s resulted in A: 92.48%, S: 95.49%, and Sp: 89.47%. Conclusion: The OA Doppler sonography has proven to be an effective and high-performance complementary imaging examination in PE diagnosis. P2 and PR were superior to the other parameters in PE diagnosis when using P2 ≥ 21.5 cm/s and PR ≥ 0.70. However, the association of both P2 and PR resulted in the best diagnostic performance regarding sensitivity. Using PR ≥ 0.75, we achieved the best Sp for PE detection.